Unloading the dice: selection and design of comparison and control groups in controlled trials to enhance translational impact within motor learning and control research. Issue 5 (3rd September 2022) - Bobrownicki, Ray; Carson, Howie J.; MacPherson, Alan C.; Collins, Dave
ABSTRACT: In order to evaluate an experimental intervention, it should be contrasted against at least one relevant comparison group. Without meaningful and relevant comparisons, results can be difficult to interpret, effect sizes may be unduly minimised or exaggerated, and any resulting recommendations for practice could be called into question. Despite recognition of the importance of control groups in study design, however, there is currently limited guidance for sport-related research with regard to the selection and design of comparison groups. Furthermore, we have become increasingly concerned with the recurrent use of comparison groups, particularly in motor learning and control studies, that may initially appear well designed in experimental terms but ultimately possess limited relevance to—and in turn limited utility for informing—applied practice. To address these issues, we first set forth and discuss the primary types of control groups available for sport research, which include no-treatment, placebo or alternative-task, variable-delivery and active-treatment groups. We then present seven key principles to consider—upon identifying the appropriate type of control—in order to maximise internal validity, enhance interpretability and best inform real-world practice for sport psychology and motor learning and development. It is intended that the principles and recommendations detailed herein could support sport-related study design to the benefit of researchers and applied practitioners alike.